Assessing swine enterprise efficiency with computerized records - Orr, D.E. Jr (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Successful swine producers must be adaptable, utilize new technology, and know their herd production levels and costs if they want to alter those production factors that have an economic impact. A summary of the effect of various production factors on swine profitability is presented, using actual herd data in composite form. These data illustrate the production and financial impact that today's technology will have on future swine production units.
Keywords: Swine; Production; Swine enterprise efficiency